SELF-REGULATED LEARNING (SRL) FIRST YEAR STUDENTS - Supriyadi Supriyadi; Debora; Ahmad Eko Suryanto (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2022)
This study aims to determine the Self-Regulated Learning (SRL) first year students in the Departement of Technology and Vocational Education (JPTK), Faculty of Teacher Training and Education (FKIP), Palangka Raya University (UPR). Zimmerman (1989) explains that to be able to carry out self regulation in learning, students/learners must regulate themselves or use certain strategies to achieve their learning goals. Pascarella & Terenzini (2005) stated that the first year is very important to identify students who may be at risk in subsequent years, so that it is considered the most optimal time to take action. This research is a quantitative research. This research to describe self-regulated learning (SRL) first year students using Zimmerman (2002) indicators, namely (1) task analysis (2) self motivational beliefs (3) self-control (4) self observation (5) self judgement and (6) self reactions. The instrument used was a questionnaire of 28 items using a Likert scale with four answer choices. The research subjects were 57 first year students in the Departement of Technology and Vocational Education (JPTK) FKIP UPR. The results showed that 10,53% of the research subject had very low Self-Regulated Learning (SRL), 38,60% of the subject were in the low category, 36,84% subject were in the high category, and 14,03% subject were in the very high Self-Regulated Learning (SRL) category. Keywords: Students, Self-Regulated Learning, First year